Vertical rootpulling resistance in maize is related to nitrogen uptake and yield - Kamara, A.; Kling, J.; Ajala, S.; Menkir, A. (2004)
Poor soil fertility and recurrent drought are major constriants to maize production in the West Africa savanna. The development of maize cultivars with superior rooting system to absorb nitrogen and water efficiently from the soil is desirable. However, direct measurement of root characteristics for rapid selection of maize lines having tolerance to the two stresses is difficult. Vertical root-pulling strenght, which has been shown to relate well to the rooting charactristics of the maize plant could be an alternative trait that can be used in improving the efficiency of selection of maize lines for tolerance to low-N stress and drought.